Provincial-level useful work and influencing factors analysis in China from 1985 to 2016: Based on logarithmic mean divisia index decomposition and affinity propagation clustering. (1st March 2019) - Xue, Yinglan; Jia, Zimu; Zeng, Weihua
Abstract: Different from conventional energy analyses which focus on primary and final stages of energy flows, useful work analysis can describe the last stage of energy transformations to end-uses. Besides, useful work analysis considers the quality of energy flows as well as efficiencies and provide a robust thermodynamic framework for analyzing the efficiency of energy use. As the world's largest energy consumer, China has less number of studies related to useful work analysis and mainly centered on national scale besides ignoring the impact of differences among different regions. Owing to this, this study developed an analysis on the temporal and spatial characteristics of useful work in China on provincial-level during 1985–2016, and combined logarithmic mean divisia index (LMDI) decomposition with affinity propagation clustering to systematically evaluate the spatial distribution of the driving factors of useful work, thereby proposing a targeted energy policy proposal for each cluster of provinces. It has been noted that the useful work of southeastern provinces has increased significantly since 1995, while western provinces had some improvements after 2005 due to the "Western Development Drive" policy. Economic output and energy intensity were the two most important factors in most of the provinces, the efficiency effect was always positive and incremental and the impact of industrial structure and energy structure were complicated. Furthermore, it could be noted that the formulation of China's energy policies should consider the features of regional useful work and their driving mechanism, and more importantly it should be adjusted in a timely manner in order to respond to different developmental stages. Highlights: A provincial-level useful work analysis of China for recent 30 years is developed. China's policies have a significant impact on energy consumption distribution. Various provinces have different driving factors of their useful work increments. An affinity propagation clustering is taken to study the peculiarity of useful work. Targeted energy policy strategies are proposed based on provincial features.